Potential Health Impacts of Heavy Metals on HIV-Infected Population in USA - Xu, Xiaohui; Hu, Hui; Dailey, Amy B.; Kearney, Gregory D.; Talbott, Evelyn O.; Cook, Robert L. (My University, 2013)
Article Authors Metrics Comments Related Content Abstract Introduction Methods Results Discussion Conclusion Author Contributions References Reader Comments (0) Media Coverage (0) Abstract Purpose Noninfectious comorbidities such as cardiovascular diseases have become increasingly prevalent and occur earlier in life in persons with HIV infection. Despite the emerging body of literature linking environmental exposures to chronic disease outcomes in the general population, the impacts of environmental exposures have received little attention in HIV-infected population. The aim of this study is to investigate whether individuals living with HIV have elevated prevalence of heavy metals compared to non-HIV infected individuals in United States. Methods We used the National Health and Nutrition Examination Survey (NHANES) 2003-2010 to compare exposures to heavy metals including cadmium, lead, and total mercury in HIV infected and non-HIV infected subjects. Results In this cross-sectional study, we found that HIV-infected individuals had higher concentrations of all heavy metals than the non-HIV infected group. In a multivariate linear regression model, HIV status was significantly associated with increased blood cadmium (p=0.03) after adjusting for age, sex, race, education, poverty income ratio, and smoking. However, HIV status was not statistically associated with lead or mercury levels after adjusting for the same covariates. Conclusions Our findings suggest that HIV-infected patients might be significantly more exposed to cadmium compared to non-HIV infected individuals which could contribute to higher prevalence of chronic diseases among HIV-infected subjects. Further research is warranted to identify sources of exposure and to understand more about specific health outcomes.
Keywords: HIV; Blood; HIV infections; Cadmium; Heavy metals; Mercury (element); Lead (element); Schools